The "Policy of Aggressive Civilization" and Projects of Governance in Roman Catholic Industrial Schools for Native Peoples in Canada, 1870-95 - Smith, Derek G. (Anthropologica, 2022)
The earliest of Canada's post-Confederation residential industrial schools for Native people are examined in light of "the Post-Foucauldian Theory of Governance," which is derived from Foucault's later work on practices governing. John L. Tobias' analysis of the periodization of Canadian policy towards aboriginal peoples is re-examined through this optic. This theoretically oriented analysis identifies three "projects of governance," which are examined in historical detail. Links of Canada's policy for residential schools are traced to the U.S. Peace Policy and other sources, and the roles of the Canadian federal government and Roman Catholic missions are re-examined.